The Biomarkers Changes in Serum and the Correlation with Quantitative MRI Markers by Histopathologic Evaluation of the Cartilage in Surgically-Induced Osteoarthritis Rabbit Model - Zuo, Houdong (PLoS One, 2015)
PURPOSE: To investigate the biomarkers change in serum and the correlation with quantitative MRI markers by histopathologic evaluation of the cartilage in surgically-induced osteoarthritis(OA) rabbit model. MATERIALS AND METHODS: Thirty-six mature New Zealand rabbits were used. Eighteen rabbits were divided into six groups randomly and equally and subjected to surgery using the improved Hulth method. The other eighteen rabbits were also allocated into six groups randomly and equally which served as the control. At multiple time points after surgery, the BMP-2, CTX-II and COMP levels in the serum were analyzed by ELISA, and quantitative MRI was performed. Histopathology was examined with HE, and Mankin scores were assessed. The changes in the biochemical biomarkers and imaging markers in the OA groups were compared with those in the control groups using paired-samples T tests. The correlation of quantitative MRI markers with biomarkers and Mankin scores were analyzed. The analysis of Mankin scores was conducted with non-parametric wilcoxon signed rank tests. RESULTS: The BMP-2 levels were increased at various times after surgery, and significant differences were observed between the OA and control groups(all the P values <0.001). CTX-II levels were significantly elevated at several intervals after surgery, including W2, W8, W12, W16 and W20(P=0.019, 0.004, 0.007, <0.001 and 0.016 respectively), but not at W4(P=0.764). Significant differences in the COMP levels from W2 to W20 were observed between the OA and the control groups(P<0.001, <0.001, <0.001, <0.001,=0.002 and =0.004 respectively). The T2 values increased at W8 post-surgery and were significantly different between the OA and control groups(P=0.001, <0.001, <0.001 and <0.001 respectively). T2* values increased from W2 to W20 and were significantly different between the control and OA groups(P=0.002, =0.001, <0.001, <0.001, =0.001 and <0.001 respectively). T2 values had significant correlation with BMP-2 and CTX-II(P<0.001 and =0.014), except COMP(P=0.305)., while the correlation of T2* values with BMP-2, CTX-II and COMP was significant(P=0.043, 0.005 and 0.025 respectively). In addition, a positive correlation of T2 values and Mankin scores was observed(P<0.001). CONCLUSION: With the relevance of the multiple time point analysis of the serum biomarkers and imaging markers compared with histological findings, BMP-2, CTX-II and COMP combined with T2 and T2* can be used to reflect and monitor OA progression potentially.